Modus Operandi Of Corruption In Government Procurement Of Goods And Services And Its Countermeasures - Darmawan, Wahyu; Djufri, Darmadi; Martini, Martini (Jurnal Ilmiah Advokasi, 2025)
In the course of national development efforts in various fields, corruption actually causes great losses for the nation, so that the public's desire to eradicate corruption and other forms of deviation is increasing. Procurement of Goods and Services (PBJ) is one of the sectors that contributes the most to corruption cases in Indonesia. The results of the study show that the modus operandi of corruption in government procurement of goods and services such as (markup) planning costs, short announcement periods, work or goods that do not meet specifications. Meanwhile, efforts to overcome corruption in government procurement of goods and services include using a competition system, opening wide access to needs, and looking at the legal track record, and Work Results. Keywords: criminal acts; corruption; procurement; goods and services